Global Profiling of Cellular Substrates of Human Dcp2 - Luo, Yang; Schofield, Jeremy A; Simon, Matthew D; Slavoff, Sarah A (Biochemistry (Easton), 2020)
Decapping is the first committed step in 5′-to-3′ RNA decay, and in the cytoplasm of human cells, multiple decapping enzymes regulate the stabilities of distinct subsets of cellular transcripts. However, the complete set of RNAs regulated by any individual decapping enzyme remains incompletely mapped, and no consensus sequence or property is currently known to unambiguously predict decapping enzyme substrates. Dcp2 was the first-identified and best-studied eukaryotic decapping enzyme, but it has been shown to regulate the stability of <400 transcripts in mammalian cells to date. Here, we globally profile changes in the stability of the human transcriptome in Dcp2 knockout cells via TimeLapse-seq. We find that P-body enrichment is the strongest correlate of Dcp2-dependent decay and that modification with m6A exhibits an additive effect with P-body enrichment for Dcp2 targeting. These results are consistent with a model in which P-bodies represent sites where translationally repressed transcripts are sorted for decay by soluble cytoplasmic decay complexes through additional molecular marks.